Modeling of a single char particle burning in oxygen-enriched O2/N2 and O2/CO2 environment with single film model. (15th November 2016) - Chen, Yuan; Sheng, Changdong
Abstract: The present work aims to clarify the influences of gas thermal properties and CO2 gasification on a single char particle burning during O2 /CO2 pulverized coal combustion based on the comparison between O2 /N2 and O2 /CO2 combustion under O2 -enriched conditions. A mathematical model was developed to describe the char particle burning in O2 /CO2 atmosphere through extending the model for O2 /N2 combustion by including CO2 gasification. The model incorporated a single-film approach, assuming no homogenous reaction in particle boundary layer. The gas properties, thermal conductivity and diffusivities, were modeled in detail to consider the transport mechanisms in the boundary layer and, particularly, the impact of gas dissociations due to high temperature O2 -enriched combustion. The model was validated with literature data, indicating its applicability to represent char burning behavior at least at O2 molar fractions of <0.2–0.3 in both O2 /N2 and O2 /CO2 combustion. It is demonstrated that, when replacing N2 by CO2, the change of gas thermal properties accounts for the most part of the decrease in char burning temperature, while CO2 gasification is responsible for 25–33% of the temperature decrease, corroborating the importance of char-CO2 gasification.